PENDETEKSIAN FRAUD DIAMOND THEORY TERHADAP PROFITABILITAS DENGAN MANAJEMEN LABA JONES THEORY SEBAGAI VARIABEL MODERATOR - Primasari, Niken Savitri (Universitas Muria Kudus, 2019)
The investor attention to earnings, might determines management's actions to take vital interests in financial reporting to show a favorable situation. Earnings management is often considered a rational and fair action principally. This manipulation is more due to the urge to keep the company's shares in demand by investors who tend to see profitability over a period of time to invest their capital in the company's shares, because for investors, because the company's profit will describe the company's overall value. This led to an increase in fraudulent actions. This study aims to analyze and find empirical evidence about the effect of fraud fraud factor based on diamond fraud, namely Pressure, Opportunity, Rationalization and Capability on financial statement fraud, which is proxied by the independent variables, namely financial stability, external pressure, financial targets, industrial conditions, ineffectiveness of supervision, audit opinions and the ability of the audit team in the financial sector to the level of profitability as the dependent variable with earnings management as moderating. All variables tend to be said to be influential except for leverage.